2020
DOI: 10.7150/ijbs.37861
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A deficiency causes islet dysfunction by inducing islet stellate cell activation via cellular retinol binding protein 1

Abstract: Background: Vitamin A (VA) plays an essential role in pancreatic homeostasis. Islet stellate cells (ISCs) are VA-storing cells in pancreatic islets. Herein, we have investigated the effect of VA on glucose homeostasis trough regulation of ISCs function in dietary VA deficiency model mice. Methods: Male C57BL/6 mice were randomly fed a VA-sufficient, a VA-deficient (VAD) or a VAD-rescued diet. Glucose metabolism was assessed by glucose tolerance tests and immunohistochemistry. ISCs activation degree was evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 27 publications
(23 citation statements)
references
References 42 publications
0
23
0
Order By: Relevance
“…Reduced β cell mass increased α cell mass, with hyperglycemia and altered serum insulin and glucagon profiles. 39 Furthermore, micronutrient deficiency may also be related to developing macro and microvascular complications of diabetes, as diabetic patients with vitamin A deficiency are also seen to develop nonhealing foot ulcers. 40 The continued high prevalence of diabetes in both young and older age groups in the Philippines suggests a complex interplay of many different factors leading to its development.…”
Section: Discussionmentioning
confidence: 99%
“…Reduced β cell mass increased α cell mass, with hyperglycemia and altered serum insulin and glucagon profiles. 39 Furthermore, micronutrient deficiency may also be related to developing macro and microvascular complications of diabetes, as diabetic patients with vitamin A deficiency are also seen to develop nonhealing foot ulcers. 40 The continued high prevalence of diabetes in both young and older age groups in the Philippines suggests a complex interplay of many different factors leading to its development.…”
Section: Discussionmentioning
confidence: 99%
“…In T2DM, ISCs transform from a quiescent into an activated state. ISCs express a large amount of α-SMA and exhibit increased proliferation and migration rates, as well as the enhanced synthesis and deposition of ECM components during activation, which are associated with fibrogenic response ( 21 , 29 ). Therefore, it is necessary to understand the mechanisms leading to the activation of ISCs in order to identify potential targets to prevent the progression of islet fibrosis in T2DM.…”
Section: Discussionmentioning
confidence: 99%
“…Mice lacking the RA-synthesizing enzyme aldehyde dehydrogenase-1 (ALDH-1) showed lower expression levels of the key gluconeogenic enzymes, glucose-6-phosphatase and phosphoenolpyruvate carboxykinase, the latter of which is an RA-inducible target gene containing a specific RA-receptor binding site as an RA response element ( 61 ). Other findings indicated an additional mechanism through which VA affects islet function by governing islets size distribution was correlated with the α-SMA-positive ISC pool in a mouse model of dietary VAD ( 29 ).…”
Section: The Protective Effects Of Va On the Pancreasmentioning
confidence: 99%
“…Zhou et al. ( 29 ) found that prolonged VA deficiency (VAD) alters the phenotype of resting islet stellate cells (ISCs, the subset of PSCs) compared with that of myofibroblast-like cells with increased α-SMA expression. Moreover, reintroduction of dietary VA to VA-deficient mice restores endocrine hormone profiles and induced ISCs/PSCs to become “re-quiescent,” similar to the results observed following induction of the VA-sufficient (VAS)-controlled ISCs/PSCs phenotype.…”
Section: Va Storage In the Pancreasmentioning
confidence: 99%
See 1 more Smart Citation